1994
DOI: 10.1111/j.1365-2222.1994.tb02742.x
|View full text |Cite
|
Sign up to set email alerts
|

Ipratropium bromide nasal spray in non‐allergic rhinitis: efficacy, nasal cytological response and patient evaluation on quality of life

Abstract: Intranasal fluorocarbon anticholinergic agents have been used to treat the nasal hypersecretion of perennial non-allergic rhinitis, but chronic use has been restricted either due to the potential for systemic anticholinergic adverse events or due to the irritating properties of the fluorocarbon metered dose formulations. This study evaluates a new aqueous nasal formulation of ipratropium bromide (Atrovent Nasal Spray 0.03%) in subjects with perennial non-allergic rhinitis in a double-blind, placebo-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…435 Intranasal anticholinergics [Summary Statements 83,84] The nasal anticholinergic ipratropium bromide is effective in reducing rhinorrhea caused by allergic rhinitis, nonallergic rhinitis (including cold-induced rhinitis 436 and gustatory rhinitis 66 ), and the common cold. [437][438][439][440][441][442][443][444][445][446][447] Ipratropium bromide is only approved (down to the age of 5 years) for the treatment of rhinorrhea, although 1 pediatric study showed modest benefit for controlling nasal congestion. 448 Ipratropium bromide has no adverse effect on physiologic nasal functions (eg, sense of smell, ciliary beat frequency, or mucociliary clearance) and has a low incidence of adverse events, in particular epistasis and nasal dryness.…”
Section: Systemic Corticosteroids [Summary Statement 81]mentioning
confidence: 99%
See 1 more Smart Citation
“…435 Intranasal anticholinergics [Summary Statements 83,84] The nasal anticholinergic ipratropium bromide is effective in reducing rhinorrhea caused by allergic rhinitis, nonallergic rhinitis (including cold-induced rhinitis 436 and gustatory rhinitis 66 ), and the common cold. [437][438][439][440][441][442][443][444][445][446][447] Ipratropium bromide is only approved (down to the age of 5 years) for the treatment of rhinorrhea, although 1 pediatric study showed modest benefit for controlling nasal congestion. 448 Ipratropium bromide has no adverse effect on physiologic nasal functions (eg, sense of smell, ciliary beat frequency, or mucociliary clearance) and has a low incidence of adverse events, in particular epistasis and nasal dryness.…”
Section: Systemic Corticosteroids [Summary Statement 81]mentioning
confidence: 99%
“…449 Atrovent (ipratropium bromide; Boehringer-Ingelheim, Ridgefield, Conn) nasal spray 0.03% has been approved for use in patients 6 years of age and older on the basis of its effectiveness in treating rhinorrhea caused by perennial allergic and nonallergic rhinitis in adults and children. [437][438][439][440][441][442] The 0.06% concentration has been approved for patients 5 years of age and older for rhinorrhea associated with the common cold. Ipratropium bromide is approved only for the treatment of rhinorrhea, although 1 pediatric study showed modest benefit for controlling nasal congestion.…”
Section: Bonementioning
confidence: 99%
“…The evidence for symptomatic relief in patients with allergic rhinitis is far more unequivocal, with nasal corticosteroids and sodium cromoglycate improving multiple symptomatic endpoints in a large number of well‐designed studies . Furthermore, ipratropium bromide produced a significant reduction in rhinorrhea and postnasal drip in 1 randomized controlled study . Endoscopic outcomes are less well reported and no improvements in these have been seen with the currently used agents in randomized controlled studies.…”
Section: Discussionmentioning
confidence: 97%
“…One surprising use of the CRQ is in studies of allergic (32) and nonallergic (19) rhinitis. In the former population, Meltzer et al (32) used the dyspnea and emotional function domains of CRQ in a double-blind, multicentre, randomized, placebo controlled, parallel group study of four weeks.…”
Section: Discussionmentioning
confidence: 99%